Liberalizacja rynku transportu lotniczego w ASEAN - Olipra, Łukasz (Liberalization of the Air Transport in ASEAN, 2008)
The article discusses the liberalization process of the air transport in ASEAN. An inspiration to study this issue was the question: whether in the South-East Asia there are any phenomena which could be called an "air regionalism". The aim of this article is the attempt to answer following questions: what are the factors of the air transport market liberalization? What influenced the ASEAN countries that they decided to start liberalization? What are the conditions of the process? What are the aims of the liberalization process and how it proceeds? To answer these questions, the Chicago Convention, bilateral agreements and the beginning of the deregulation and liberalization processes have been outlined. Then there is a short characteristic of open skies agreements presented. Next there are issues concerning the ASEAN countries: general conditions of transport in ASEAN, co-operation in transport, differences among member countries and the ASEAN Transport Action Plan for 2005-2010. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 28, s. 167-179